ANALISIS MISKONSEPSI SISWA KELAS X SMA DI KOTA PADANG TENTANG MATERI HUKUM NEWTON DENGAN MENGGUNAKAN TES DIAGNOSTIK FOUR-TIER MULTIPLE CHOICE - Bawamenewi, Amisa (Physics Learning and Education, 2024)
The importance of students' understanding of concepts is to enhance the learning process and achieve good learning outcomes. However, what often happens is that students struggle to understand the material, make mistakes in applying concepts, and even become frustrated or lose interest in certain subjects. This research aims to describe students' misconceptions through a four-tier multiple-choice diagnostic test on Newton's laws. This study is a qualitative descriptive research using a four-tier multiple-choice test instrument. The research sample includes three public high schools in the city of Padang in the academic year 2023/2024. The sampling technique used is simple random sampling, with 25% of the total number of students in each school participating in the study, totaling 80 students. Based on the analysis, the highest level of understanding of concepts experienced by students is in the subtopic of Newton's Third Law, with an average percentage of 57.3%. Meanwhile, the highest misconceptions experienced by students are in the subtopics of the applications of Newton's Laws I, II, III, with average percentages of 84.6%, 76.3%, and 85%, respectively. Additionally, the highest lack of understanding of concepts is in the subtopic of forces on inclined planes, with a percentage of 40%. Therefore, it can be concluded that in Newton's laws, there are more misconceptions experienced by students.